Akuntabilitas Layanan Surat Izin Mengemudi Keliling di Jawa Tengah - Muji Ediyanto; Kismartini Kismartini; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
This study aims to analyze the accountability of mobile driving license (SIM) services. Service accountability is the accountability of public service providers to the community for every decision and action. Instead, accountability is a motivation for all stakeholders to be responsible for the services provided to realize good governance. This research has a qualitative-descriptive approach with the research location in the working area of the Central Java Regional Police. Data were obtained through in-depth interviews, field observations and documentation. The results showed that the performance of the Ditlantas Polda Central Java was not optimal. This is indicated by the discrepancy between the mobile SIM service product and the number of owners of passenger cars and motorcycles. This condition is influenced by the quantity and quality of human resources/employees, the lack of collaboration with other parties and the low level of socialization to the community. The mobile SIM service facility is also the cause of the low performance of the Central Java Police Ditlantas. The car as a service key facility is not adequate. On the other hand, offline mobile SIM services are still found in the Central Java region. This service is not integrated, thus reducing the quality of mobile SIM services, especially for immigrants who are not from other regions. The conclusion is that the accountability of the Central Java Police Ditlantas regarding mobile SIM services is still relatively low. So that to increase the accountability of the Central Java Police Ditlantas, they must carry out an evaluation to rearrange plans and concepts, build collaboration and increase socialization related to mobile SIM services.